REDEFINISI PRINSIP PEMBEDAAN DALAM HUKUM HUMANITER INTERNASIONAL DI ERA PERANG DRONE: STUDI KASUS GAZA DAN UKRAINA - Mawan Sutanto, Dwi; Karyana, Rana; Hanla, Hanla; Susilo, Tarsius; Setia, I ketut; Iskandar, Yulian (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The development of combat drone technology has revolutionized the landscape of modern warfare, but also presents new challenges to the fundamental principles of International Humanitarian Law (IHL), particularly the principle of distinction between combatants and civilians. This article examines the ethical and legal dilemmas of drone usage through a qualitative normative juridical approach, using case studies from the Gaza conflict (Israel vs. Hamas) and the Russia–Ukraine war. The analysis reveals that despite drones offering high precision, field practices often demonstrate violations of the principle of distinction, whether due to intelligence negligence or policies that relax the definition of combatants. The technological imbalance of drone warfare also risks eroding humanitarian values and dehumanizing victims. This study underscores that technological advancement must be accompanied by the strengthening of legal accountability, the integration of ethics into military procedures, and the adaptation of operational rules to uphold humanitarian principles in warfare. Therefore, redefining the application of the principle of distinction is necessary to address the challenges of remote drone-based warfare, in order to ensure that the value of life remains protected amidst the escalation of military technology